Faces of Justice - Krasoń, Robert (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
Justice is undoubtedly the foundation of the existence and functioning of a democratic state under the rule of law, the formation of social relations, and an essential factor for building and deepening trust. In turn, the concept itself appears as undefined, vague, often described as unclear. Justice has had, has and probably always will have two faces – positive and negative. Under no circumstances should it be interpreted as a one-time, momentary burst of emotion, triggered by some impulse from the outside, but as a skill of reason acquired by long-term moral effortand will. Justice has accompanied mankind since the beginning of time. It is a peculiar phenomenon, the essence of which has been pondered over the centuries by the great minds of the world: philosophers, poets, biblical authors. Thinking about justice, we intuitively sense that it is one of the most important issues for humanity in general – an all-encompassing issue.